Product lifecycle management for digital transformation of industries : 13th IFIP WG 5.1 International Conference, PLM 2016, Columbia, SC, USA, July 11-13, 2016, Revised selected papers /: 13th IFIP WG 5.1 International Conference, PLM 2016, Columbia, SC, USA, July 11-13, 2016, Revised selected papers. (2016) - Unknown
No abstract available